Eukaryotic Membranes and Cytoskeleton Origins and Evolution - Jékely, Gáspár (Advances in Experimental Medicine and Biology, 2007)
Eukaryotic Membranes and Cytoskeleton: Origins and Evolution discusses the evolutionary origin and diversification of eukaryotic endomembranes and cytoskeleton from a cell biological and comparative genomic perspective. Many of the chapters present original research data from comparative genomic surveys. The presence/absence of gene families with central roles in endomembrane and cytoskeleton dynamics in a variety of eukaryotic taxa and an understanding of eukaryote phylogeny allow us to accurately reconstruct the cellular machineries present in the last common ancestor of eukaryotes. Such a reconstruction is fundamental if we are to understand eukaryotic diversification since this is the ancestral cell from which all diversity arose. Comparative genomics can likewise tell us which lineages expanded or reduced certain gene families and the associated cellular machineries.